The Flexibility of the Ego among High School Students - Marfoo, Hiraa Amin; Manukh, Sabah Marshoud (Journal of Tikrit University for Humanities, 2023)
The current research aims to identify: - - The level of the ego flexibility among high school students according to gender, (males - females). ـ The level of the ego flexibility among high school students according to according to specialization, (literary – scientific). The current research community consists of secondary school students the academic year2023/2022 . The research sample was (300) from high school students. The researcher used statistical methods (t-test for one sample, t-test for two different samples, Pearson and Wackronbach correlation coefficient). The researcher reached the following results:- 1- The secondary school students have an average level of flexibility in analytics. 2ـ There are statistically significant differences in the level of resilience I, according to the variables of sex, (males – females). 3ـ There are no statistically significant differences in the level of flexibility according to the change of specialization, (literary – scientific). Keywords: flexibility, ego, high school